UJI STABILITAS FISIK SEDIAAN MASKER GEL PEEL-OFF EKSTRAK ETANOL DAUN KENITU (Chrysophyllum cainito L.) - Gina Septiani Agustien; Nitya Nurul Fadilah; Dina Fitri Nusyifa (Jurnal Insan Farmasi Indonesia, 2022)
Kenitu leaves contain flavonoids which function as antioxidants that can counteract the bad effects of free radicals, the antioxidant effect will be better if formulated in topical dosage forms. One of the topical dosage forms for use on the face is a peel-off gel mask, its use is easy to remove like an elastic membrane. This study aims to determine the physical stability of the peel-off gel mask preparation of kenitu leaves ethanol extract. The research method was experimental by making three peel-off gel mask formulations based on variations in extract concentration, namely F1 (2%), F2 (4%) and F3 (8%). Evaluations were carried out on the physical stability of the preparation, including organoleptic observations, homogeneity, pH, adhesion, dispersibility, drying time of the preparation, and viscosity. The results showed that the physical stability test of the peel-off gel mask preparation of kenitu leaves ethanol extract could be formulated in the form of a peel-off gel mask preparation, and the best mask formula was F1 with an extract concentration of 2%.